2019
DOI: 10.1177/0891243219869365
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Happiness Gap: The Decline of Gendered Parenthood Norms and the Increase in Parental Life Satisfaction

Abstract: In recent decades, normative expectations for parenthood have changed for both men and women, fertility has declined, and work–family arrangements have become more egalitarian. Previous studies indicate that the transition to parenthood and work–family arrangements both influence life satisfaction and do so differently for men and women. Drawing on constructivism and utility maximization, we theorize how gendered parenthood norms influence life satisfaction after the transition to parenthood, and how decisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 68 publications
(103 reference statements)
0
16
0
Order By: Relevance
“…The higher the number of children, the greater the effect of employment stability on life satisfaction for men compared with women. Preisner et al ( 27 ) showed that the parenthood happiness gap between men and women decreased with the decline in gendered parenthood norms. However, this study verifies that Korea's stratified labor market characteristics affect parental life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the number of children, the greater the effect of employment stability on life satisfaction for men compared with women. Preisner et al ( 27 ) showed that the parenthood happiness gap between men and women decreased with the decline in gendered parenthood norms. However, this study verifies that Korea's stratified labor market characteristics affect parental life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the only predictor of the patterns of the depressed mood trajectory for the fathers was the subjective judgment that their current financial situation was not sufficient to pay for the family living expenses. A study tracing the socio-economic panel data in Germany from 1984 to 2015 found that the weakening of gendered parenthood norms has contributed to overall life satisfaction in fathers and mothers [15]. Gender norms continue to play an essential role between parenthood and men's and women's psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Parents in different countries may perceive the burden and stress caused by the cultural norms and expectations toward parenthood. Gendered parenthood norms contribute to the differences in psychological well-being among fathers and mothers in different societies [15]. For instance, a study conducted in Jordan suggested that first-time fathers' postpartum experiences are influenced by cultural beliefs of masculinity that inhibit their involvement in caring for their spouses and babies, as well as their expression of psychological distress [16].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to new social regulations that promote work-life balance and reduce social and economic pressures, as well as the availability of more egalitarian ways of parenting, the degree of women's satisfaction after becoming mothers has apparently increased (Preisner et al, 2020). Still, mothers often feel overburdened and penalized by the demands of combining work and family (Molina & Montuenga, 2009), making them experience ambivalent emotions caused by gender archetypes and expectations (Almond, 2011).…”
Section: Contextmentioning
confidence: 99%